Essays on credit and default under the presence of collateral - Yan, J (2018)
This thesis is a collection of three essays, which study a range of topics related to leverage, credit and default under the presence of collateral. The essay on belief disagreement and leverage proposes a novel approach in general equilibrium frameworks to assess how beliefs affect equilibrium and contract origination. Binding collateral constraints raise asset prices above the fundamental value. The model establishes that changes in market average belief rather than belief disagreement drives the asset price movement. The essay on mortgages and Minsky effect presents a micro-founded framework to study the macroeconomic effect of mortgage default, and shows that the endogenous leverage of the mortgage contract together with the bank capital determine the comovement of prices, leverage and credit extension. Default is more severe after good states than after bad states, due to high leverage and risk-taking. Minsky effect amplifies the financial instability. The essay on systemic risk measurement presents a calibration method for equilibrium models of banking systems, identifies channels that co-determine the distress dependence structures in the banking system, and the results suggest that the “Minsky effect”, in addition to the widely accepted feedback channels such as the interbank lending and common exposure, serves as a systemic risk amplification mechanism.